Imidazole-carbazole conjugate for two-photon-excited photodynamic therapy and fluorescence bioimaging - Pham, Thanh Chung; Lee, Dong Joon; Kim, Do Hun; Yoon, Juyoung; Lam, Tran Dai; Kim, Hwan Myung; Lee, Songyi (Chemical Communications, 2023)
A heavy-atom-free photosensitizer (CI) based on an imidazole-carbazole conjugate exhibited strong fluorescence emission and ROS generation via both type I and II mechanisms. In particular, CI showed efficient photodynamic therapy and fluorescence bioimaging under two-photon (TP) excitation (740 nm) toward HeLa cells with negligible dark toxicity.
Keywords: Bio-imaging; Fluorescence emission; Heavy atoms; HeLa cell; Imidazol; Photosensitiser; Two-photon excitations; Two-photon excited; Carbazoles; Fluorescence; HeLa Cells; Humans; Imidazoles; Photochemotherapy